Fabrication, characterization and optimization of in-house MOSFET transistor using spin on dopant technique - Morsin, Marlia (2004)
This thesis explains the development and fabrication of first in-house MOSFET device using spin -on dopant technique at KUKUM Microfahrication Cleanroom. The process started with the establishment of process flow, process modules, and process parameters. Four modules were developed. The characteristics prior to the MOSFET device fabrication namely dry and wet oxidation, etching, resist thiclrness, exposure dose optimization, n-type and p-type spin on dopant and diffusion and also metal thiclrness characterization were recorded. The data were analyzed and applied in the fabrication of MOSFET devices. The MOSFET fabrication process llsed blanket-field oxide for isolation, positive resist for lithography process, Boron and Phosphorus for source/drain doping and aluminum for metallization. The whole MOSFET process had fOllT masking process specifically source/drain masking, gate masking, contact masking, and metal masking. The result for each processes are presented in this thesis.